A High‐Efficiency Hematite Photoanode with Enhanced Bonding Energy Around Fe Atoms. Issue 12 (29th January 2021) - Lan, Yangchun; Kang, Shuai; Cui, Dehu; Hu, Zhuofeng
Abstract: Hematite nanoarrays are important photoanode materials. However, they suffer from serious problems of charge transfer and surface states; in particular, the surface states hinder the increase in photocurrent. A previous strategy to suppress the surface state is the deposition of an Fe‐free metal oxide overlayer. Herein, from the viewpoint of atomic bonding energy, it is found that the strength of bonding around Fe atoms in the hematite is the key to suppressing the surface states. By treating the surface of hematite with Se and NaBH4, the Fe2 O3 transforms to a double‐layer nanostructure. In the outer layer, the Fe−O bonding is reinforced and the Fe−Se bonding is even stronger. Therefore, the surface states are inhibited and the increase in the photocurrent density becomes much faster. Besides, the treatment constructs a nanoscale p–n junction to promote the charge transfer. Improvements are achieved in onset potential (0.25 V shift) and in photocurrent density (5.8 times). This work pinpoints the key to suppressing the surface states and preparing a high‐efficiency hematite nanoarray, and deepens our understanding of hematite photoanodes. Abstract : Hematite photoanodes : By treating the surface of hematite with Se and NaBH4, the Fe2 O3 is transformed into a double‐layer nanostructure. In the outer layer, the Fe−O bonding is reinforced and the Fe−Se bonding is even stronger. Therefore, the surface states are inhibited and the increase in photocurrent density becomes much faster.